Effect of graphene filler on mechanical properties of cotton/viscose hybrid composite. Issue 3 (14th March 2022) - Arunkumar, K.; Raghu, R.; LetaTesfaye, J.; Krishnaraj, R.
Abstract: This work addresses the preparation of cotton/viscose fabric reinforced hybrid composite with graphene as a filler material by a compression moulding process and investigation on their mechanical properties such as tensile strength, flexural strength, impact strength, and hardness. The graphene filler was taken in different proportions such as 1.5 weight percentage (wt. %), 3 wt. %, and 4.5 wt. %, which was mixed with the matrix material. It was observed that the addition of filler improved the mechanical properties of the composite. The hybrid composite with 4.5 wt. % of graphene was observed with an enhanced tensile strength of 73.9 MPa and flexural strength of 406.2 MPa. An improvement of 21.7 % in tensile strength and 284.2 % in flexural strength was noticed for the addition of 4.5 wt. % of graphene filler. The addition of filler during the preparation of hybrid composite improved the bonding of the epoxy matrix with the cotton/viscose fabric and thereby mechanical properties were enhanced due to better load carrying capacity of the composites. Abstract : The tensile strength of cotton/viscose hybrid composite incorporated with graphene filler has been studied. Higher graphene filler volume fraction, leads to a better tensile strength of the composite.